(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
This article is about improving the ability of speaking in English and the students’ perspective on it. There are several different kinds of methods which can be fruitful in developing students’ oral skills. Most essential methods are discussed in this article.